2021
DOI: 10.1186/s12935-020-01741-7
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA VPS9D1-AS1 facilitates cell proliferation, migration and stemness in hepatocellular carcinoma

Abstract: Background Hepatocellular carcinoma (HCC) is a common cancer leading to high morbidity and mortality in worldwide. Previous studies revealed that SEC61 translocon alpha 1 subunit1 (SEC61A) can act as an oncogene in colon adenocarcinoma. However, the functions and molecular mechanism associated with HCC progression remain to be explored. This study aimed at exploring the role of SEC61A1 in HCC progression. Methods EdU assay and colony formation assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Preliminary evidence suggests that the anticancer effects of sorafenib in HCC patients are related to these mechanisms. e results of previous studies have confirmed that SLC41A3, SEC61A1, LRP4, PPM1G, and HSP90AA1 play important roles in cancer progression [28][29][30][31][32][33][34][35][36][37][38][39]. SLC41A3 is a member of solute carrier family 41 and is involved in many cellular processes.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Preliminary evidence suggests that the anticancer effects of sorafenib in HCC patients are related to these mechanisms. e results of previous studies have confirmed that SLC41A3, SEC61A1, LRP4, PPM1G, and HSP90AA1 play important roles in cancer progression [28][29][30][31][32][33][34][35][36][37][38][39]. SLC41A3 is a member of solute carrier family 41 and is involved in many cellular processes.…”
Section: Discussionmentioning
confidence: 77%
“…miR-491-5p inhibits HCC cell proliferation and migration by regulating SEC61A1 expression. VPS9D1-AS1 can upregulate SEC61A1 expression by sponging miR-491-5p, which in turn is involved in HCC growth and metastasis [ 30 ]. PPM1G is overexpressed in HCC tissues and associated with HCC metastasis, the pathological grade, microvascular invasion, and hepatitis B virus (HBV) infection.…”
Section: Discussionmentioning
confidence: 99%
“…One of its regulators, miR-30a-5p, also has been widely of concern as an important miRNA, especially for its role via crosstalk with other RNAs in some pathways in different cancers (67)(68)(69). The overexpression of another ncRNA, lncRNA VPS9D1-AS1, a potential prognostic marker, can be used to predict poor prognosis in NSCLC (70), and its role in cancer has been validated (71,72). All of these RNAs have been validated with roles in tumorigenesis, and this axis may be a proper marker to predict cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased miR-491-5p and highly pyruvate kinase M2 (PKM2) expression were associated with unfavorable clinical features and the poor prognosis of HCC patients [ 46 ]. In addition, overexpressed miR-491-5p inhibited HCC cell proliferation and migration by targeting SEC61 translocon alpha 1 subunit1 (SEC61A) [ 47 ]. The inhibition effect of lenvatinib in sorafenib-resistant HCC cells occurred partially through miRNA regulation.…”
Section: Discussionmentioning
confidence: 99%